Aspecte jurisprudențiale privind relațiile personale dintre copil și părinții săi// Jurisprudential Aspects regarding the Personal Relations between the Child and his Parents - Lucia Irinescu (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice, 2022)
The superior interest of the child, within the meaning of Law no. 272/2004 and of the Civil Code, is limited to the child's right to a normal physical and moral development, to a socio-affective balance and to family life, a right also affirmed by art. 8 of the European Convention on Human Rights. The child has the right to grow up with both his parents, who are responsible for his upbringing and education. In the situation where the parents do not live together, the possibility of the parent with whom the child was not present to have personal relations with him must be recognized as high as possible.